Atlastin-1 regulates morphology and function of endoplasmic reticulum in dendrites - Xianzhuang Liu (Nature Portfolio, 2019)
The molecular mechanisms that achieve ER morphology in neurites are not well understood. This study uses a forward genetic approach to demonstrate that atln-1 is required for neuronal ER morphology and that C. elegans atln-1 mutants exhibit defects in mitochondria fission at dendritic branch points and abnormalities in protein homeostasis.